2011
DOI: 10.1002/anie.201102698
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Open‐Framework Selenidostannates Synthesized in Ionic Liquids

Abstract: Ready to direct: Crystalline selenidostannates were synthesized in imidazolium‐based ionic liquids with a small amount of hydrazine monohydrate as additive (see scheme). They are the first open‐framework chalcogenides structurally directed by imidazolium cations and are inaccessible by traditional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 39 publications
2
56
0
1
Order By: Relevance
“…For instance, research from our own and Dehnen's groups showed that a combination of ILs and an organic amine as auxiliary solvent was an efficient system for the fabrication of selenidostannates, in which the organic amine and the IL cations might co-induce specific structures. 24,25 Similar phenomena have been observed in the ionothermal syntheses of zeolites; [26][27][28][29] for example, a new open-framework aluminophosphate with a unique Al/P ratio was synthesized by using an amine and ILs as co-templates. 26, 29 Thus we realize that syntheses in ILs with different SDAs would produce highly novel structures due to the chemical and compositional flexibility of SDAs.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…For instance, research from our own and Dehnen's groups showed that a combination of ILs and an organic amine as auxiliary solvent was an efficient system for the fabrication of selenidostannates, in which the organic amine and the IL cations might co-induce specific structures. 24,25 Similar phenomena have been observed in the ionothermal syntheses of zeolites; [26][27][28][29] for example, a new open-framework aluminophosphate with a unique Al/P ratio was synthesized by using an amine and ILs as co-templates. 26, 29 Thus we realize that syntheses in ILs with different SDAs would produce highly novel structures due to the chemical and compositional flexibility of SDAs.…”
Section: Introductionmentioning
confidence: 61%
“…7, all the weight losses correspond to the losses of organic components and H 2 Se molecules. 24 The post-TGA residues for the four compounds were identified as a mixture of MnSe, SnSe and/or SnSe 2 (Fig. S8-S11 †) by PXRD.…”
Section: Powder X-ray Diffraction Analyses and Thermal Propertiesmentioning
confidence: 99%
“…In order to obtain chalcogenides with novel structures and unique properties, several synthetic methods have been developed, such as high-temperature solid-state reactions, room-temperature solution processes, hydrothermal/solvothermal methods, and recently emerged ionthermal/surfactantthermal methods [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Mild solvothermal method has been proven to be an efficient approach to prepare these materials.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic strategy using mixed transitiontransition (d-d) and transition-rare earth metal (d-f), have been reported widely. In contrast, the heterometallic frameworks based on the 13 main metal and transition metal with organic aromatic carboxylic acid ligands have been explored relatively rare, such as [In 3 O(BBDC) 3 12 ]Á(solvent) x [9]. Such investigation is still limited, and the synthesis methods for these compounds have been rather limited to hydro/solvothermal method.…”
Section: Introductionmentioning
confidence: 98%
“…Ionothermal synthesis, using ionic liquid as solvent, has been shown to be a highly promising synthetic route for a wide variety of MOFs [10][11][12]. In recent years, this method has received remarkable attention because of the outstanding properties of the ILs: nonflammability, negligible vapor pressure, high polarity, and so forth.…”
Section: Introductionmentioning
confidence: 99%